2015
DOI: 10.3109/17435390.2014.984251
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular and mitochondrial dysfunction in the female F1 generation after gestational TiO2nanoparticle exposure

Abstract: Due to the ongoing evolution of nanotechnology, there is a growing need to assess the toxicological outcomes in under-studied populations in order to properly consider the potential of engineered nanomaterials (ENM) and fully enhance their safety. Recently, we and others have explored the vascular consequences associated with gestational nanomaterial exposure, reporting microvascular dysfunction within the uterine circulation of pregnant dams and the tail artery of fetal pups. It has been proposed (via work de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 77 publications
1
43
1
Order By: Relevance
“…Together with a lack of response to nitric oxide, these findings indicate that exposure compromised the normal microvascular dilation in fetal vasculature [141]. Further studies demonstrated that microvascular dysfunction coincided with a reduction in the maximal mitochondrial respiration in both cardiac and uterine tissues [142]. These results indicate that prenatal NM exposure impairs microvascular function in the offspring and may persist through multiple developmental stages.…”
Section: Cardiovascular Systemmentioning
confidence: 88%
“…Together with a lack of response to nitric oxide, these findings indicate that exposure compromised the normal microvascular dilation in fetal vasculature [141]. Further studies demonstrated that microvascular dysfunction coincided with a reduction in the maximal mitochondrial respiration in both cardiac and uterine tissues [142]. These results indicate that prenatal NM exposure impairs microvascular function in the offspring and may persist through multiple developmental stages.…”
Section: Cardiovascular Systemmentioning
confidence: 88%
“…This may be related to preferential accumulation of PM within the mitochondria (96) and dysregulation of the respiratory chain complexes I and III in rat brain tissue, leading to an increased generation of ROS (38). These mitochondrial alterations may be long lasting with generational consequences (114).…”
Section: Future Directions/studiesmentioning
confidence: 98%
“…Evidence exists of DNA damage, including single-and double-strand breaks and DNA-protein crosslinks (72); altered overall DNA content (11); as well as mitochondrial DNA methylation (18), following exposure to xenobiotic particles. Furthermore, xenobiotic particles may penetrate to the endoplasmic reticulum and trigger the unfolded protein response, a signaling cascade initiated by the intracellular accumulation of misfolded proteins, as well as oxidative stress (129), a response that may also involve the mitochondria (49,78,107,114) (Fig. 3C).…”
Section: Xenobiotic Particlesmentioning
confidence: 99%
“…However, few studies have examined such outcomes following exposure to NP. An investigation that examined the effects of titanium dioxide exposure during pregnancy in rats revealed microvascular impairments in the maternal uterine arterioles that resulted in cardiac mitochondrial insufficiency in the offspring that persisted through adulthood (Stapleton et al, 2013, 2014). In our previous studies, pregnant mice were exposed by inhalation to CdO NP, and while Cd was not measurable in the fetus, there were effects on neonatal growth (Blum et al, 2012) and sex-dependent dyslipidemia in adult offspring fed a high-fat diet (report in preparation).…”
mentioning
confidence: 99%